A novel approach for three-dimensional evaluation of reduction morphology in distal radius fracture - Yuichi Yoshii; Yusuke Eda; Reo Asai; Akira Ikumi; Yasukazu Totoki; Sho Kohyama; Takeshi Ogawa (BMC Musculoskeletal Disorders)
Abstract Background Distal radius fractures are among the most common fractures, traditionally evaluated using two-dimensional (2D) parameters. These methods are unreliable in significantly displaced fractures, with discrepancies among evaluators. Recent advancements in imaging have introduced three-dimensional (3D) models, but standard parameters for 3D reduction morphology are not well established. This study aimed to develop a novel method for evaluating 3D reduction morphology based on the normal vector of a plane defined by anatomical reference points, comparing the reduction shape to the mirror image of the unaffected contralateral side. Methods This retrospective case-control study included 27 patients (mean age 67.6 years) who underwent osteosynthesis with a volar locking plate for distal radius fractures. Preoperative and postoperative computed tomography (CT) scans of the affected and unaffected wrists were analyzed using 3D image analysis software. The 3D coordinates of three reference points; (1) radial styloid process, (2) sigmoid notch volar edge, and (3) sigmoid notch dorsal edge, were used to evaluate the reduction shape and compare it to the unaffected side mirror image. Correlations between vector angles in the coronal, sagittal, and axial planes and clinical outcomes, such as % total active motion (%TAM) and Mayo wrist scores, were analyzed. Results The distances between the unaffected mirror image and postoperative image for the three reference points were 2.1 mm, 2.1 mm, and 2.7 mm, with barycenter differences of 1.7 mm. The postoperative plane areas consisted from three reference points were significantly larger in the postoperative image compared to the unaffected mirror image (203.4 mm² vs. 192.4 mm², P < 0.01). Correlation coefficients for vector angles in the yz-plane between unaffected mirror image and postoperative image were moderate (0.58, P < 0.05). Mild correlations were found between postoperative vector angles in the xy and xz planes and %TAM. Conclusions This novel 3D evaluation method provides a more comprehensive assessment of fracture reduction, particularly in the axial plane. While it demonstrates good reproducibility in coronal alignment, further refinement is needed for sagittal and axial alignments. This method could enhance surgical precision and improve clinical outcomes in distal radius fracture management. Clinical trial number Not applicable.